Earth's changing climate - Wolfson, Richard (Chantilly, VA : Teaching Co., 2007)
Twelve lectures on climate change and global warming presented by Professor Wolfson.
Is Earth warming? -- Butterflies, glaciers, and hurricanes -- Ice ages and beyond -- In the greenhouse -- A tale of three planets -- Global recycling -- The human factor -- Computing the future -- Impacts of climate change -- Energy and climate -- Energy, resources and alternatives -- Sustainable futures.
Keywords: Climatic changes; Global warming